2021
DOI: 10.1002/pen.25845
|View full text |Cite
|
Sign up to set email alerts
|

Development of thermo‐regulating fabrics with enhanced heat dissipation via graphene‐modified n‐octadecane microcapsules

Abstract: Phase change materials (PCMs) are of great importance in thermal regulation applications, but low thermal conductivity is the most critical disadvantage of these materials. Especially in the textile field, while there are many studies on the production of PCM-coated fabrics, studies on improving heat dissipation are quite limited. Therefore, in this study, first, n-octadecane was encapsulated with melamine formaldehyde shell modified with graphene as a thermal conductivity enhancer, and then, synthesized PCM m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 66 publications
(91 reference statements)
0
6
0
Order By: Relevance
“…Microencapsulation of FAS was performed according to an improved method reported by Hicyilmaz and Li. [27,28] Figure 1 illustrates the process of preparing microcapsules containing FAS with a UF shell. The whole process was divided into three steps: (1) First, 6 g of urea, 12 g of formaldehyde and 30 ml of deionized water were mixed.…”
Section: Preparation Of Microcapsulesmentioning
confidence: 99%
“…Microencapsulation of FAS was performed according to an improved method reported by Hicyilmaz and Li. [27,28] Figure 1 illustrates the process of preparing microcapsules containing FAS with a UF shell. The whole process was divided into three steps: (1) First, 6 g of urea, 12 g of formaldehyde and 30 ml of deionized water were mixed.…”
Section: Preparation Of Microcapsulesmentioning
confidence: 99%
“…The introduction of a 60% mass fraction of the thermal filler improved the thermal conductivity to 0.358 W/mK, leading to an enhanced heat dissipation performance. Sezer et al coated polyester fabrics with phase change microcapsules containing n-octadecane in a melamine-formaldehyde shell, , and found that a small amount of graphene load (0.1 wt %) increased the thermal conductivity by 31%, thereby improving the heat dissipation ability of the fabric. Fan et al developed a layered fabric utilizing electrospinning and dipping techniques, consisting of styrene-ethylene-butylene-styrene (SEBS), a nonwoven inner layer, and Al 2 O 3 treated SEBS/SEBS-F127.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, MPCMs with high encapsulation efficiency and large heat transfer area can avoid the inherent disadvantages of PCMs. Therefore, MPCMs are increasingly used in building energy savings, [10][11][12] textiles, [13][14][15] thermal management of electronics, 16,17 and solar power utilization. 18,19 A considerable amount of literature focusing on the preparation and thermal performance of MPCMs has been published.…”
Section: Introductionmentioning
confidence: 99%